Keroncong Ambyaran”: Inovasi dalam Pembawaan Keroncong oleh Keroncong Syahdu di Semarang - Khoiruddin, Nur Faqih Imam; Abdul Rachman, S.Pd, M.Pd (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
Keroncong music, as one of Indonesia's cultural heritages, is often considered outdated by the younger generation. However, the development of contemporary music presents opportunities to revitalize this genre. This article explores the innovation of "Keroncong Tapi Ambyaran," a new approach to presenting keroncong that blends traditional musical elements with the theme of heartbreak (ambyar) characteristic of today's youth. This study employs a qualitative method through in-depth interviews with modern keroncong musicians and analysis of musical works. The findings indicate that this approach successfully captures the interest of young people through the use of relatable lyrics, fresh arrangements, and collaborations with musicians across genres. Furthermore, social media plays a significant role in disseminating and popularizing this concept. The study concludes that "Keroncong Tapi Ambyaran" not only preserves the traditional values of keroncong but also makes it relevant to the younger generation, paving the way for the sustainability of keroncong music in the modern era.